Diabetes and depression comorbidity and socio-economic status in low and middle income countries (LMICs): a mapping of the evidence - Leone Tiziana; Coast Ernestina; Narayanan Shilpa; de Graft Aikins Ama (BMC, 2012)
Abstract Non-communicable diseases account for more than 50% of deaths in adults aged 15-59 years in most low income countries. Depression and diabetes carry an enormous public health burden, making the identification of risk factors for these disorders an important strategy. While socio-economic inequalities in chronic diseases and their risk factors have been studied extensively in high-income countries, very few studies have investigated social inequalities in chronic disease risk factors in low or middle-income countries. Documenting chronic disease risk factors is important for understanding disease burdens in poorer countries and for targeting specific populations for the most effective interventions. The aim of this review is to systematically map the evidence for the association of socio-economic status with diabetes and depression comorbidity in low and middle income countries. The objective is to identify whether there is any evidence on the direction of the relationship: do co-morbidities have an impact on socio-economic status or vice versa and whether the prevalence of diabetes combined with depression is associated with socio-economic status factors within the general population. To date no other study has reviewed the evidence for the extent and nature of this relationship. By systematically mapping the evidence in the broader sense we can identify the policy and interventions implications of existing research, highlight the gaps in knowledge and suggest future research. Only 14 studies were found to analyse the associations between depression and diabetes comorbidity and socio-economic status. Studies show some evidence that the occurrence of depression among people with diabetes is associated with lower socio-economic status. The small evidence base that considers diabetes and depression in low and middle income countries is out of step with the scale of the burden of disease.